Parenting interventions for empowering emotionally-intelligent parents: a proposed study to parents of preschool children in Selangor - A. G., Siti Fatimah; Kadir Shahar, Hayati; Awang, Hamidin; Othman, Mohd Sukki; Abdul Rahman, Anita (Community Health Society Malaysia, 2014)
Background: Parents play a crucial role in establishing later patterns of emotional, cognitive and social functioning in children. Parenting practices affect children in various ways, for instance, children’s behaviour, school achievement and emotional intelligence. One of the best ways to empower parenting practices is through parenting intervention program. In doing so, theories usually are employed as guidance. Examples of the theories used are Behavioural Change Theories and Attachment Theory. Behaviour-based parenting intervention focuses on changing parenting behaviours that lead to a change in children behaviours. Whilst, Attachment-based or emotion-based parenting focuses on changing children behaviour by regulating parents’ and children’s emotion. From Islamic perspective, Muslim believed that Prophet Muhammad salallahu alaihi wasallam (s.a.w) is the best role model for parenting. Therefore, this paper is aimed to develop an Islamic Parenting Program which holistically covers all domains of well-being, namely physical, emotional, behavioural and spiritual.